(untitled) (Annals of Medical Research, 2024)
Aim: Examining the symptoms and effects of fibromyalgia in patients with nasal septum deviation which is an important cause of nasal deformity. Materials and Methods: Seventy eight patients with nasal septum deviation and 78 healthy volunteers similar in age and gender were included in the study. Patients with systemic rheumatic disease, cardiovascular system disease, infectious disease, any other disease that may affect the respiratory passage other than nasal septum deviation, with a history of regular drug use, and under the age of 18 were not included in the study. Widespread pain score and symptom severity score were calculated for all participants according to the fibromyalgia syndrome American College of Rheumatology 2016 diagnostic criteria, and revised fibromyalgia impact questionnaire was filled out. Results: While the incidence of fibromyalgia syndrome was higher in patients with septal deviation, this difference was not statistically significant (p=0.072). There was no difference between the groups in terms of widespread pain score, symptom severity score, total score and revised fibromyalgia impact questionnaire score (p=0.438; p=0.933; p=0.502; p=0.081, respectively). Conclusion: Although no significant relationship has been found between fibromyalgia and septal deviation, further studies on this subject should be conducted.